2020
DOI: 10.1177/1550147720949133
|View full text |Cite
|
Sign up to set email alerts
|

Swarm intelligence–based energy efficient clustering with multihop routing protocol for sustainable wireless sensor networks

Abstract: Wireless sensor network is a hot research topic with massive applications in different domains. Generally, wireless sensor network comprises hundreds to thousands of sensor nodes, which communicate with one another by the use of radio signals. Some of the challenges exist in the design of wireless sensor network are restricted computation power, storage, battery and transmission bandwidth. To resolve these issues, clustering and routing processes have been presented. Clustering and routing processes are consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…This proposed IPSO-GWO method gave excellent results as it provided the greatest possible energy efficiency with a lifetime of the network. To determine the efficiency of this strategy, Energy efficiency measure was used to calculate the amount of energy used by each node over the course of a given time period [47]. Hussen, used the Backpropagation network and the K-Means algorithm to cluster groups of diverse medical data.…”
Section: Application Of Artificial Intelligent Techniques In Data Clu...mentioning
confidence: 99%
“…This proposed IPSO-GWO method gave excellent results as it provided the greatest possible energy efficiency with a lifetime of the network. To determine the efficiency of this strategy, Energy efficiency measure was used to calculate the amount of energy used by each node over the course of a given time period [47]. Hussen, used the Backpropagation network and the K-Means algorithm to cluster groups of diverse medical data.…”
Section: Application Of Artificial Intelligent Techniques In Data Clu...mentioning
confidence: 99%
“…Jiang et al proposed an energy-balanced unequal clustering (EBUC) communication protocol able to partition the sensor network and turns them into many uneven clusters [26]. Hence, one source communicates to the base station via a multi-hop channel [27]. This way, any node with the highest energy level can promote itself to become a CH.…”
Section: Related Workmentioning
confidence: 99%
“…It is observed that the absence of TDMA leads to wastage of energy. For improvement, Lee et al discussed the utility of an energy-efficient scheme call the Location-based Unequal Clustering Algorithm or LUCA [27]. LUCA localizes the nodes and forms CHs depending on the cluster's distance Malaysian Journal of Computer Science, Vol.…”
Section: Related Workmentioning
confidence: 99%
“…Because of its flexible nature, MANET is highly relevant in disaster relief, battlefield communications, educational, and commercial, emergency, search and rescue operations. The key challenge in MANETs is the development of dynamic routing protocol which could be aware of mobility and effective for determining the routes among the transmitting nodes with less overhead and better performance [4]. The routing protocol in MANET is classified into 3 classes according to how routing information is maintained and acquired using mobile nodes.…”
Section: Introductionmentioning
confidence: 99%